Synthetic generation of streamflow data using computer simulation model - Leven K V (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1993)
A Study has been made to develop a computer simulation model for the synthetic generation of streamflow data for Chaliyar, one of the larger basins of the state.